Ventricular septal rupture with right hypochondrial pain mimicking acute cholecystitis. Issue 6 (June 2022) - Urabe, Daichi; Kawakami, Daisuke; Nishigaki, Haruna; Miyoshi, Yusuke; Ito, Jiro; Ueta, Hiroshi; Shimozono, Takahiro; Mima, Hiroyuki
Abstract: A 67-year-old man was admitted for anterior acute ST elevation myocardial infarction (STEMI) management. He developed a severe acute right subcostal pain with normal cardiac tests. On day 5 of hospitalization, cholecystectomy was performed for suspected acute cholecystitis, but the pain intensified with hemodynamical instability. Transthoracic echocardiography revealed ventricular septal rupture (VSR). After emergency operation was performed, the pain diminished with improved hemodynamics. Right subcostal pain associated with heart disease can be referred from STEMI or liver congestion with right heart failure. VSR and right heart failure may be considered as a cause of right subcostal pain of uncertain etiology. <Learning objective: Patients presenting with signs suggestive of acute cholecystitis may be misdiagnosed, and we highlight the importance of considering ventricular septal rupture as a differential diagnosis.>